2021
DOI: 10.1371/journal.pone.0253852
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomic and transcriptomic analysis reveals endogenous substrates and metabolic adaptation in rats lacking Abcg2 and Abcb1a transporters

Abstract: Abcg2/Bcrp and Abcb1a/Pgp are xenobiotic efflux transporters limiting substrate permeability in the gastrointestinal system and brain, and increasing renal and hepatic drug clearance. The systemic impact of Bcrp and Pgp ablation on metabolic homeostasis of endogenous substrates is incompletely understood. We performed untargeted metabolomics of cerebrospinal fluid (CSF) and plasma, transcriptomics of brain, liver and kidney from male Sprague Dawley rats (WT) and Bcrp/Pgp double knock-out (dKO) rats, and integr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 117 publications
4
7
0
Order By: Relevance
“…We found that riboflavin was significantly elevated in both Bcrp single-and Bcrp/P-gp double-knockout mice, those with deficiency of Bcrp (1.5and 1.6-fold, respectively) (P < 0.05; Figure 2C and Table 1), suggesting that Bcrp may play an important role in the circulation levels of the vitamin in mice. This is consistent with the 2.64fold increase of plasma riboflavin concentration in Bcrp/P-gp double-knockout rats compared to wild-type animals previously reported (Ganguly et al, 2021). By contrast, riboflavin, was not significantly changed in the P-gp single-knockout mice compared with the control (P > 0.05, fold change: 0.9; Figure 2C and Table 1), indicating riboflavin was not a substrate for P-gp.…”
Section: Metabolomic Analyses Of Plasma From Bcrp and P-gp Knockout M...supporting
confidence: 91%
“…We found that riboflavin was significantly elevated in both Bcrp single-and Bcrp/P-gp double-knockout mice, those with deficiency of Bcrp (1.5and 1.6-fold, respectively) (P < 0.05; Figure 2C and Table 1), suggesting that Bcrp may play an important role in the circulation levels of the vitamin in mice. This is consistent with the 2.64fold increase of plasma riboflavin concentration in Bcrp/P-gp double-knockout rats compared to wild-type animals previously reported (Ganguly et al, 2021). By contrast, riboflavin, was not significantly changed in the P-gp single-knockout mice compared with the control (P > 0.05, fold change: 0.9; Figure 2C and Table 1), indicating riboflavin was not a substrate for P-gp.…”
Section: Metabolomic Analyses Of Plasma From Bcrp and P-gp Knockout M...supporting
confidence: 91%
“…Hence, the metabolites identified in our experiments may not be direct substrates of Pgp, and these metabolic alterations could be a secondary response to transporter inhibition. In a study with BCRP/Pgp double knock-out rats, metabolites including creatinine, threonine, pantothenate, glutamine, phenylalanine, methionine and nicotinamide were identified to be altered in CSF or plasma; however, none of these metabolites could be indicated as Pgp substrates based on in silico prediction of Pgp interaction [ 38 ]. Although this study highlighted the impact of BCRP and Pgp ablation on systemic metabolome rather than intracellular changes, it is interesting to identify alterations in identical metabolites in CSF which suggests the significance of these metabolites and associated metabolic pathways in a neurological context.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, reduced plasma membrane BCRP localization has been observed in hyperuricemia, allowing the accumulation of uric acid and preventing its excretion [ 42 , 45 ]. In one study, Ganguly et al reported elevated CSF levels of a few purine metabolism metabolites in rats lacking Pgp and BCRP transporters [ 38 ]. It is still not clear how BCRP inhibition results in reduced cellular hypoxanthine and xanthine levels however one possible explanation is that it could be a compensatory response induced by impaired uric acid transport to reduce uric acid production.…”
Section: Discussionmentioning
confidence: 99%
“…11 It is involved in modulation of absorption, distribution, and excretion of drugs and environmental chemicals as well as endogenous and dietary compounds, 12 affecting their tissue distribution. 13,14 Interactions between the ABCG2 efflux transporter and some tryptophan-related metabolites from the kynurenine pathway have already been described by our group using targeted metabolomic analysis. 15 Our previous findings support the role of ABCG2 in the secretion into milk of tryptophan, kynurenic acid, kynurenine, anthranilic acid, and xanthurenic acid, but melatonin metabolites were not considered and only endogenous levels were analyzed.…”
Section: Introductionmentioning
confidence: 98%
“…ABCG2 represents the major route for active secretion of toxins, drugs, vitamins, and natural compounds into milk 10 and is also expressed in the apical membrane of cells from important organs for xenobiotic disposition such as the liver, intestine, kidney, and blood–brain barrier, among others 11 . It is involved in modulation of absorption, distribution, and excretion of drugs and environmental chemicals as well as endogenous and dietary compounds, 12 affecting their tissue distribution 13,14 . Interactions between the ABCG2 efflux transporter and some tryptophan‐related metabolites from the kynurenine pathway have already been described by our group using targeted metabolomic analysis 15 .…”
Section: Introductionmentioning
confidence: 99%